Cultivation of mushroom pleurotuseous and quantitative Estimation of secondary metabolites With antioxidant activity - K.SHOBA,; Dr. S.KRISHNAKUMARI, (International Journal of Pharma and Bio Sciences, 2017)
Mushroomis an attractivecrop to cultivate in developing countries for many reasons. Secondary metabolites serve as competitive weapons.The present study focuses on cultivation and yield of Pleurotus eous and quantification of secondary metabolites like flavonoids, phenols and tannins in aqueous and methanol extract of mushroom and also the study was conducted to determine the antioxidant potential of extracts using in-vitro reducing antioxidant power assay with standard methods.The result showed that the mushroom yield was estimated and it shows high bio-efficiency.Secondary metabolites of methanolic extract had the highest flavonoids, phenols and tannin content followed by aqueous extract and also it showed that antioxidant potential of reducing power of mushroompleurotus extract demonstrated the highest reducing power in the methanolic extract than the aqueous extract. It exhibited significant differences (P<0.05) in their antioxidant values. Increase in the absorbance indicates increase in the reducing power. It can be concluded from the study that the bioactive compounds of mushroom used for curing various human diseases.